Multi-Intervention of Balance Exercise to Prevence of Fall Risk among Vertigo Patient - Musthofa, Faizal; Kosim, Kosim; Fitria, Nita; Maulana, Sidik (iora, 2022)
The condition of vertigo if left unchecked will endanger the patient. Vertigo has an impact on quality of life which includes limitations in carrying out daily activities, the risk of falling and can result in injury. This study was conducted to determine the multi-intervention of balance exercise in preventing the risk of falling in vertigo patients. A rapid literature review was conducted on this study related to multi-intervention balance exercises in preventing the risk of falls in vertigo patients from the PubMed, CINAHL, and Science Direct databases. Inclusion criteria for vulnerable full text research articles in 2017-2021 using English. Balance exercise with vestibular rehabilitation, balance retraining, wobble board exercise can be one way to prevent the risk of falling by maintaining balance in vertigo patients and being able to reduce dizziness symptoms, improve quality of life, compliance in exercise and improve dizziness symptoms. Most studies say that balance exercise interventions with vestibular rehabilitation, balance retraining, and wobble board exercises are effective in improving balance, reducing dizziness symptoms in vertigo patients as a prevention of the risk of falling